Optimization of regional median equations of prenatal screening markers for trisomy 21 in a Chinese population. Issue 35 (August 2018) - Xu, Liangpu; Huang, Hailong; Zheng, Lin; He, Deqin; Lin, Na; Wang, Linshuo; Lin, Yuan
Abstract : Abstract: To establish gestational age-specific and body weight-specific mid-trimester normal median equations for the prenatal serum markers α-fetoprotein (AFP), free β subunit human chorionic gonadotropin (fβHCG), and unconjugated oestriol (uE3) for a Chinese population; to compare and replace the median equations built in LifeCycle software; to evaluate the effect of equations used for gestation correction on estimating risk in Down's syndrome, Edward's syndrome, and neural tube defect (NTD). A total of 353, 065 cases of prenatal screening data of pregnant women were screened by 13 prenatal screening institutions in China. The local median equations of each institution and the large data were fitted by the least square regression, and then the difference was compared between large data equations and local median equations. The applicability of the localized median equations was evaluated by the determination coefficient. Based on the established median equations, multiples of median (MoM) of each values were calculated and compared with the latest Down's syndrome quality assurance support service (DQASS). There is no significant difference between the local median equations of each institution and the large sample median equations, which are various from LifeCycle built-in median equations. Besides, the determination coefficient of localized median equations are >0.99. 97.0% MoM medians obtained by using local median equations are consistent with latest standard of DQASS. The median established by large sample data represents the median level of a Chinese population, and can be used to replace the software built-in median equations to achieve better screening results.